Solve Using the Square Root Property x(x-1)=0

Math
x(x-1)=0
If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.
x=0
x-1=0
Set the first factor equal to 0.
x=0
Set the next factor equal to 0 and solve.
Tap for more steps…
Set the next factor equal to 0.
x-1=0
Add 1 to both sides of the equation.
x=1
x=1
The final solution is all the values that make x(x-1)=0 true.
x=0,1
Solve Using the Square Root Property x(x-1)=0

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top